Hubungan Iklim Organisasi dengan Kekerasan pada Perawat - Teguh Mitra Surya; Syarifah Rauzatul Jannah; Fithria Fithria (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the relationship between organizational climate and workplace violence in nurses at the Aceh General Hospital. The method used is descriptive quantitative research design cross sectional study. The results showed that there was a significant relationship between organizational climate (p=0.000) and workplace violence in nurses at the Aceh General Hospital. The conclusion is that the better the organizational climate, the less the potential for workplace violence. The participation of hospital management is needed to prevent all forms of violence, therefore the hospital needs a good organizational climate by committing together in changing and creating a safe environment, facilitating staff needs, and controlling staff performance to achieve common goals. Keywords: Organizational Climate, Violence, Nurse